Religious Harmony, Godly Nationalism, and the Limits of State-sponsored Interreligious Dialogue Agenda in Indonesia - Imam Sopyan; Pepen Irpan Fauzan; Ahmad Khoirul Fata (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: This paper discus the discourse of religious harmony in Indonesia by looking into the role played by PKUB/FKUB, a state-sponsored body focused on maintaining religious harmony, in the context of interreligious dialogue agenda in Indonesia. By looking into its trajectory and legal standing, this paper hypothesizes that there are some limits within the PKUB/FKUB in addressing the spirit and practice of interreligious dialogue to the Indonesian public due to the preference of religious harmony rather than interreligious dialogue. This paper then wants to explore the preference of religious harmony by employing Godly-Nationalism/Productive Intolerance concept. The data of this paper is collected by library research methodology. Finally, this paper suggests that despite the discourse of religious harmony requires the religious community to engage in the dialogue, there is a different direction and objective to which the dialogue would lead. While the dialogue in the context of religious harmony would be directed to maintaining harmony itself, the interreligious dialogue as suggested by several scholars requires religious people to learn from others to change and grow together. Keywords: Interreligious Dialogue, Religious Harmony, PKUB, FKUB, Godly- Nationalism.